Classification of TRIZ Techniques Using a Cognition-Based Design Framework. (2015) - Samuel, Philip; Ohler, Michael
Abstract: The role of the Theory of Inventive Problem Solving (TRIZ) techniques within engineering design is examined through the lens of Cognition- based Design (CBD). The paper aims to answer some of the questions sought by the design community at large and to provide some directions for scholars and practitioners on how TRIZ techniques can be applied during various stages of the design process. The CBD framework is based on a systems-view that integrates core principles coming from traditional engineering design with fundamental concepts as they are used in cognitive psychology and other fields related to cognition (e.g., problem solving, creativity, and learning theory). The paper provides the details of the proposed cognition-based classification scheme for TRIZ techniques. This is illustrated with the help of the CBD framework. The classification scheme is based on three components: (1) the stage of the design process in which TRIZ techniques are applied and the primary cognitive function supported by the technique; (2) the cognitive level required for mastery of the technique; and (3) the cognitive style simulated through the technique. The aim of this classification scheme is to help design practitioners and TRIZ students make better choices about the techniques they will use, based on the challenges of the given design opportunity, rather than choosing only those techniques they are familiar with. Recommendations are given for making use of the new classification scheme and guidelines for future research. That research can also identify potential loopholes in the problem solving process and techniques, as they are currently available to the designer.